PENERAPAN MODEL PEMBELAJARAN DIRECT INSTRUCTION DENGAN PENDEKATAN SAVI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI ASAM BASA KELAS XI SMA (UNESA Journal of Chemical Education, 2019)
This research aims to describe the learning implementation of Direct Instruction learning model with SAVI, student activity and student learning outcomes. This research used “One Group Pretest-Posttest Design” with the subject of research were 32 student of class XI MIPA 7 SMAN 1 Manyar Gresik. The results of this research showed that (1) The implementation of more than 2.1 with very good category with the quality of implementation at the first meeting was 3.44 (very good), the second meeting was 3.60 (very good and the third meeting was 3.89 (very good) (2) The time spent on somatic activity amounted to 28% of the total time at the first meeting, at 26% of the total time at the second meeting, and 25.3% of the total time at the third meeting. The time spent on auditory and visual activities amounted to 12% of the total time at the all meetings. The spent on intellectual activity amounted to 12% of the total time at first meeting, at 11.33% of the total time at the second meeting, and 10.67% of the total time at the third meeting. This indicated that the students have activity and study the acid-base material well (3) Student learning outcomes obtained by 94% achieving classical completeness. Gain score of 93.75% student get category improvement of learning result height and 6.25% student get category improvement of result of learning medium. Gain score of 93.75% of students obtained gain score were high categories and 6.25% of students obtained gain score were medium category.Keywords: Direct Instruction, SAVI, learning outcomes